Pros and Cons of the Impact Factor in a Rapidly Changing Digital World - McAleer, Michael; Oláh, Judit; Popp, József (Journal of Reviews on Global Economics, 2018)
The purpose and novlty of the paper is to present arguments for and against the use of the Impact Factor (IF) in a rapidly changing digital world. The paper discusses the calculation of IF, as well as the pros and cons of IF. Editorial policies that affect IF are examined, and the merits of open access online publishing are presented. Scientific quality and the IF dilemma are analysed, and alternative measures of impact and quality are evaluated. The San Francisco declaration on research assessment is also discussed.